Local increase of anticyclonic wave activity over northern Eurasia under amplified Arctic warming - Daokai Xue; Jian Lu; Lantao Sun; Gang Chen; Yaocun Zhang (Geophysical Research Letters)
Abstract In an attempt to resolve the controversy as to whether Arctic sea ice loss leads to more midlatitude extremes, a metric of finite‐amplitude wave activity is adopted to quantify the midlatitude wave activity and its change during the period of the drastic Arctic sea ice decline in both ERA Interim reanalysis data and a set of Atmospheric Model Intercomparison Project‐type of model experiments. Neither the ensemble mean response to the trend in the SST nor that to the declining trend of Arctic sea ice can replicate the sizable midlatitude‐wide increase in the total wave activity (Ae) observed in the reanalysis, leaving its explanation to the atmospheric internal variability. On the other hand, both the diagnostics of the flux of the local anticyclonic wave activity (LAWA) and atmospheric general circulation model experiments lend evidence to a possible linkage between the sea ice loss near the Barents and Kara Seas and the increasing trend of LAWA over the northern part of the central Eurasia and the associated impacts on the frequency of temperature extremes.